Illusive : contemporary illustration / Part four - Klanten, Robert, 1964-; O'Reilly, John, ....- (Berlin : Gestalten, 2015)
Whether as a complement to written content or a stand-alone attention getter, illustration is being used more and more often to set prominent accents. Illustrations have become a key component of advertising, communication, reporting, and other media. Because visual storytelling gets messages across more effectively in our age of information overload, illustration is gaining in importance. It's no wonder that the current spectrum of creative expression represented by this technique is so vast. Illusive 4 is the definitive reference of contemporary illustration and these developments. Showcasing the work of around 200 active illustrators --both established names and new talents --from around the world, the book demonstrates the dynamism of this creative technique and documents global trends. Some examples surprise the viewer by integrating elements from fashion sketching, figurative painting, collage, and photography. Astute texts describe how and where illustration is being used today and put the featured work into context. They explore opportunities for illustration in fields including advertising and merchandising and for thematic topics such as fashion, lifestyle, politics, and culture. Illusive 4 makes it clear that illustrations are not only used as decorative elements, but to visually convey both content and emotions. Because of its role as a transmitter of information, the medium of illustration is not limited by current fads. In fact, much of the included work is characterized by an impressive creative independence. The results are as astounding as they are inspiring. Its scope makes Illusive 4 a rich source of ideas for illustrators, painters, and visual artists, as well as for graphic and editorial designers. Its combination of images and text offers added insights for editors, writers, and anyone working in communication. In short, the book is meant for everyone who is passionate about